Cellular and General Resistance of Young Futsal Players Aged 13-16 Years Depending on Blood Group according to the ABO System - Dychko, Danil; Dychko, Elena; Dychko, Vladislav; Zhuk, Vadym; Shayda, Natalya (International Journal of Statistics in Medical Research, 2026)
Relevance: Regular physical activity during adolescence affects immune adaptation, but the possible contribution of genetically determined ABO blood group phenotypes to interindividual variability in immune resistance remains insufficiently substantiated. Purpose: This study aimed to determine the features of cellular, innate (general) and acquired immune resistance in young futsal players aged 13–16 years, taking into account ABO blood group phenotype. Materials and Methods: A total of 75 boys aged 13–16 years were examined: 45 futsal players and 30 practically healthy peers who did not engage in organized sports. Peripheral blood parameters were analyzed, including leukocytes, granulocytes, agranulocytes, neutrophil subpopulations, lymphocytes, monocytes, erythrocytes, hemoglobin and erythrocyte sedimentation rate (ESR). The adaptation index (AI) was calculated as the lymphocyte-to-segmented neutrophil ratio. Statistical analysis included assumption checking, pairwise comparisons with correction for multiple subgroup testing, and additional reporting of 95% confidence intervals, Cohen’s d effect sizes and observed power for AI comparisons. Results: Most young futsal players demonstrated cellular and general immune resistance indicators corresponding to physiological adaptation. In athletes with O(I), A(II) and B(III) blood groups, AI corresponded to calm activation. In the AB(IV) subgroup, AI was lower than in controls and reached nominal statistical significance; however, this finding should be interpreted cautiously because of the very small subgroup size and loss of confirmatory strength after correction for multiple comparisons. Conclusions: The study suggests that systematic futsal training in adolescents is generally associated with physiological immune adaptation. The possible relationship between ABO phenotype and immune adaptation requires verification in larger, longitudinal and statistically powered samples.